Analisis Determinan Makro Ekonomi Pada Beberapa Negara Asia dalam Memepengaruhi TKI Tahun 2011-2015 - Matius Inganta Purba; Risni Julaeni Yuhan (Universitas Muhammadiyah Sidoarjo, 2018)
Asia is the country with the largest number of TKI placement. However, from 2012 there was a decrease in the number of overseas placement for Indonesians even in the four year interval there was a decrease up to 52.66 percent including in Asian countries. One of the causes of the decline of labor migrants is due to the revamping of the placement of informal TKI in some countries, especially in the middle east region so that the number of migrant workers is very small. In fact, the remittance of migrant workers is one of the largest foreign exchange contributors in Indonesia. In 2011, the value of remittance reached 60 trillion or the second highest contributor of foreign exchange. Of course with the existence of such remittances can support the Indonesian economy. The purpose of this study is to see what variables that influence in the process of placement of overseas workers especially in some countries in Asia continent based on economic condition of destination country. Analytical techniques used are panel data analysis with inflation variable, per capita income, unemployment rate, and exchange rate of destination country. The results of this study indicate that the variables of inflation, income per capita, and unemployment rate in influencing the number of placement of labor migrants in the destination country.